2018
DOI: 10.1111/desc.12688
|View full text |Cite
|
Sign up to set email alerts
|

The independent and interacting effects of socioeconomic status and dual‐language use on brain structure and cognition

Abstract: Family socioeconomic status (SES) is strongly associated with children's cognitive development, and past studies have reported socioeconomic disparities in both neurocognitive skills and brain structure across childhood. In other studies, bilingualism has been associated with cognitive advantages and differences in brain structure across the lifespan. The aim of the current study is to concurrently examine the joint and independent associations between family SES and dual-language use with brain structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 102 publications
(121 reference statements)
4
38
1
Order By: Relevance
“…Consistent with several previous investigations of the associations of socioeconomic status (SES) with gray matter morphology in samples spanning wide age ranges (Brito & Noble, 2018;Brito et al, 2017;McDermott et al, 2019;Noble et al, 2015), we found that INR was associated with volume in several areas of the association cortex. Specifically, we found that cortical regions associated with language, mentalizing, theory of mind, and emotion (Yarkoni et al, 2011)-including areas of the fusiform gyrus, inferior frontal gyrus, middle frontal gyrus, superior frontal gyrus, and inferior and superior temporal gyri-were sensitive to INR in FAMILY INCOME, BRAIN VOLUME, ADOLESCENCE 23 interaction with biological sex in early adolescence and/or longitudinally from early to later adolescence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with several previous investigations of the associations of socioeconomic status (SES) with gray matter morphology in samples spanning wide age ranges (Brito & Noble, 2018;Brito et al, 2017;McDermott et al, 2019;Noble et al, 2015), we found that INR was associated with volume in several areas of the association cortex. Specifically, we found that cortical regions associated with language, mentalizing, theory of mind, and emotion (Yarkoni et al, 2011)-including areas of the fusiform gyrus, inferior frontal gyrus, middle frontal gyrus, superior frontal gyrus, and inferior and superior temporal gyri-were sensitive to INR in FAMILY INCOME, BRAIN VOLUME, ADOLESCENCE 23 interaction with biological sex in early adolescence and/or longitudinally from early to later adolescence.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have used whole-brain approaches to examine the associations between SES and cortical thickness and surface area. In large samples of children, adolescents, and young adults from the multi-site Pediatric Imaging, Neurocognition, and Genetics study, higher family income was associated with greater cortical surface area, with the strongest effects in brain regions that support language and executive function, including the bilateral inferior temporal, insula and inferior frontal gyri, and in the right occipital and medial prefrontal cortex (Brito & Noble, 2018;Brito, Piccolo, & Noble, 2017;Noble et al, 2015). In a another large sample of participants ages 5-25 years, there were positive associations between SES (family income and parental education) and cortical surface area in regions supporting FAMILY INCOME, BRAIN VOLUME, ADOLESCENCE 5 sensorimotor processing, emotion regulation, language, and memory, including bilateral regions of the lateral prefrontal, anterior cingulate, lateral temporal, and superior parietal lobule (McDermott et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Because 33 out of the 41 children, or 80% our sample, came from low SES environments, this finding supports the recent claim that enhancements in neural functioning associated with dual language experience are not restricted to high SES environments (Krizman, Skoe, & Kraus, 2016). Although we did not have data from enough dual language learners with high SES to test for an interaction between dual language experience and SES, given the recent report of an interaction between these two variables in terms of brain structure (Brito & Noble, 2018), future functional MRI studies with larger cohorts should aim to elucidate the extent to which language experience and SES interact to drive changes in neural variability in cognitive systems during development.…”
Section: Socioeconomic Influences On Neural Activation Variabilitysupporting
confidence: 83%
“…Besides dual language experience, an important factor that influenced neural activation variability was SES. Although examining neural activation variability in relation to SES was not a primary aim of this study, we included this variable as a covariate because of previous work showing that socioeconomic factors such as parental education are associated with brain development and brain-behavior relationships related to reading (Hackman & Farah, 2009;Noble et al, 2015;Noble, Wolmetz, Ochs, Farah, & McCandliss, 2006), as well as decreased neural response consistency to speech sounds (Skoe, Krizman, & Kraus, 2013), and furthermore can interact with dual language experience to influence brain structure and cognition (Brito & Noble, 2018). The current pattern of results was such that lower SES was associated with a reduction in neural activation variability within the same cortical region that showed enhancements in relation to dual language experience.…”
Section: Socioeconomic Influences On Neural Activation Variabilitymentioning
confidence: 99%
“…In another study that tested effects of bilingualism on grey matter, Brito and Noble (2018) compared cortical thickness and surface area between monolinguals and bilinguals, aged between 3 and 21 years. Several covariates were included in their analyses, including age, sex, socioeconomic status, and genetic ancestry.…”
Section: Bilingualism and Brain Developmentmentioning
confidence: 99%